Marxian Microfoundations: Contribution or Detour? - Goldstein, Jonathan P. (The Review of radical political economics, 2006)
This article celebrates and critically examines the twenty-five-year productive, yet highly controversial, Marxian microfoundations (MM) literature. The contentious methodological debate over MM that is dominated by fundamentalist positions on both sides is evaluated and rejected. An alternative, centrist, methodological defense of MM is developed. Having established a methodological basis for MM, the micro contributions of the existing literature are evaluated in the following subject areas: methodology, accumulation and crisis, labor process and labor market segmentation, technical change, and class and exploitation. I conclude that although the MM literature has made significant contributions to strengthening Marxian arguments/propositions, there is room for improvement in the areas of integrating existing MM with common themes, improving modeling techniques, developing better linkages between micro and macro behaviors, expanding the analysis to neglected topics, and empirically verifying underlying assumptions.